Protocol for a scoping review of implementation research approaches to universal health coverage in Africa - Charles S Wiysonge; Chukwudi A Nnaji; Prosper Tumusiime; Joseph Okeibunor; Thobile Malinga; Abdu A Adamu; Humphrey Karamagi (BMJ Open)
Introduction Implementation research has emerged as part of evidence-based decision-making efforts to plug current gaps in the translation of research evidence into health policy and practice. While there has been a growing number of institutions and initiatives promoting the uptake of implementation research in Africa, their role and effectiveness remain unclear, particularly in the context of universal health coverage (UHC). This review aims to extensively identify and characterise the nature, facilitators and barriers to the use of implementation research for assessing or evaluating UHC-related interventions or programmes in Africa.Methods and analysis This scoping review will be developed based on the methodological framework proposed by Arksey and O’Malley and enhanced by the Joanna Briggs Institute. It will be reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines. A comprehensive search of the following electronic databases will be conducted: Medline (via PubMed), Scopus and the Cochrane Library. Relevant grey literature and reference lists will also be searched. All publications describing the application of implementation research in the context of UHC will be considered for inclusion. Findings will be narratively synthesised and analysed using a predefined conceptual framework. Where applicable, quantitative evidence will be aggregated using summary statistics. There will be consultation of stakeholders, including UHC-oriented health professionals, programme managers, implementation researchers and policy-makers; to provide methodological, conceptual and practical insights.Ethics and dissemination The data used in this review will be sourced from publicly available literature; hence, this study will not require ethical approval. Findings and recommendations will be disseminated to reach a diverse audience, including UHC advocates, implementation researchers and key health system stakeholders within the African region. Additionally, findings will be disseminated through an open-access publication in a relevant peer-reviewed journal.